A new species of Pseudancistrus from the Rio Caroni Venezuela (Siluriformes: Loricariidae) - Armbruster, Jonathan W.; Taphorn, Donald C. (Zootaxa, 2008)
Pseudancistrus reus is a new species from the Río Caroní (Río Orinoco drainage) of Venezuela known from two individuals. It differs from all other Pseudancistrus by having a color pattern consisting of alternating dark and light bars. In addition, it differs from all except P. genisetiger and P. papariae by having an incomplete mid-dorsal plate row and from P. genisetiger and P. papariae by having 18 contiguous mid-dorsal plates vs. 14 plates, a plateless break and then two more plates at the end of the caudal peduncle. The type locality of P. reus was submerged by the construction of the Caruachi dam, and is also the only known locality of the gymnotiform Sternarchorhynchus gnomus, making it imperative that the conservation status of these and other potential Caroní endemics be assessed. Pseudancistrus reus is the first species of Pseudancistrus sensu stricto from the Orinoco. Although the relationship of the species to other Pseudancistrus is unknown, P. reus may have gained access to the Orinoco either via stream capture between the Caroní and the Rio Uraricoera (Rio Branco – Rio Negro drainage) or via stream capture between the Caroní and either the Cuyuní or Mazaruni Rivers (Essequibo River drainage).key word: Siluriformes, Loricariidae, taxonomySe describe como especie nueva Pseudancistrus reus del río Caroní (cuenca del río Orinoco) en Venezuela, basada en dos ejemplares. Difiere de todas los demás Pseudancistrus en tener un patrón de pigmentación que consiste de barras claras alternando con oscuras. Además, difiere de todas los demás, menos P. genisetiger y P. papariae en tener la fila medio-dorsal de placas incompleta, y de P. genisetiger y P. papariae difiere en tener 18 placas medio-dorsales contiguas vs. 14 placas seguidas por una zona sin placas y luego dos placas más en el pedúnculo caudal). La localidad típica de P. reus fue sumergida por las aguas del embalse Caruachi. Ese sitio es también la localidad típica de Sternarchorhynchus gnomus, haciéndolo imprescindible evaluar el estado de conservación de estas dos especies más las otras endémicas del bajo Caroní. Pseudancistrus reus es la primera especies de Pseudancistrus sensu stricto de la cuenca del río Orinoco. Aunque desconocemos las relaciones con otras Pseudancistrus, P. reus puede haber ganado acceso al Caroní vía la captura de caños en las cabeceras del río Uraricoera-Branco-Negro o del río Cuyuní o Mazaruni, afluentes del río Essequibo.